Limit Circle/Limit Point Criteria for Second-Order Sublinear Differential Equations with Damping Term - Jing Shao; Wei Song (Abstract and Applied Analysis)
The purpose of the present paper is to establish some new criteria for the classification of the sublinear differential equation as of the nonlinear limit circle type or of the nonlinear limit point type. The criteria presented here generalize some known results in the literature.